The role of office atmospherics on enhancing internal marketing effectiveness in fulfilling job satisfaction: an application to the shipping industry - Panigyrakis, George G.; Yerimou, Pantelitsa; Kyriacou, Evdoxia (My University, 2020)
Managers are continually adopting sensory stimuli in their integrated marketing communication strategies to influence consumers’ behavior. However, marketing literature does not provide evidence of managers’ and employees’ responses about internal environmental stimuli and the effect on their behavior in the service sector. This research in-progress, examines how the use of atmospheric elements in the workplace can influence and enhance internal marketing effectiveness in fulfilling employees’ job satisfaction. Using a mixed-method approach of interviews and questionnaires, employees in shipping companies will evaluate the use of sensory stimuli in their working environment and the impact on their level of satisfaction. Results obtained will be used to fill important theoretical and practical gaps.
Keywords: Atmospherics; Sensory stimuli; Internal marketing; Integrated marketing; Job satisfaction